Multisite Evaluation of Veterans Treatment Courts: Systematic Assessment of Implementation and Intermediate Outcomes, Florida, North Carolina, and Texas, 2016-2019 - Baldwin, Julie Marie ([Verlag nicht ermittelbar], 2024)
The purpose of this study was to conduct a comprehensive multi-site examination of veterans treatment court (VTC) operations through an implementation and intermediate outcome evaluation. The focus was primarily on VTC processes and participant populations, as well as basic participant outcomes. Both quantitative and qualitative data were collected from baseline and follow-up interviews, self-report survey data, semi-structured observations, and official records from eight VTC programs in three states. Users should note that qualitative data are not available as part of this study at this time. It is not known when these data might be made available.